Assessment of Terrestrial Carbon Sinks in China Simulated by Multiple Vegetation Models - Weiyi Xu; Jing Liu; Longgao Chen; Suchen Ying (Land)
China plays an important role in the global terrestrial carbon cycle. While China is included in global assessments of the carbon cycle, such as the global carbon budget, the performance of dynamic global vegetation models (DGVMs) over China has rarely been evaluated. This knowledge gap constrains both model applicability and region-specific parameter optimization within China. To address this gap, our study assesses the performance of terrestrial carbon stocks and sinks simulated by 12 DGVMs in China from 1970 to 2018. The results indicate that (1) there is significant variation in the numerical magnitudes of terrestrial carbon stocks as simulated by various models, with mean vegetation carbon at 38.3 PgC and mean soil carbon at 115.3 PgC. Nevertheless, their spatial distribution demonstrates a remarkable degree of congruence. Notably, the simulated carbon stocks are generally in excess of existing estimates. (2) Despite the good consistency in the spatial distribution of terrestrial carbon sinks across different models, there is considerable fluctuation in the numerical values, with a mean carbon sink of 0.02 PgC yr−1, a value lower than pre-existing estimations. (3) The responses of terrestrial carbon stocks and sinks to CO2 fertilization, climate change, and land use change exhibit pronounced heterogeneity. CO2 fertilization has a positive effect, whereas land use change has a negative one. The impact of climate change is variable, and the carbon sink effect engendered by CO2 fertilization is negated by the adverse influence of land use change. This comprehensive evaluation of the simulation performance of DGVMs in China is anticipated to serve as an important reference for the functional analysis and parameter optimization of DGVMs within China.